Diffuse idiopathic skeletal hyperostosis and axial spondyloarthritis—similarities and differences - David Kiefer; Muhammad Asim Khan; Xenofon Baraliakos (Exploration of Musculoskeletal Diseases)
Diffuse idiopathic skeletal hyperostosis (DISH) and axial spondyloarthritis (axSpA) are diseases with inflammatory involvement of the axial skeleton that can result in new bone formation that may lead to total ankylosis of the spine and functional impairment of different extent in individual patients. In these diseases, the new bone formation may lead to total ankylosis of the spine and impaired mobility with functional impairment. This review will highlight the similarities and differences of these two conditions. In axSpA, the genetic background with the association with human leukocyte antigen-B27 (HLA-B27) is known for 50 years, while in DISH, a genetic contribution is not yet proven. The phenotype of new bone formation and its anatomic features are different between these diseases. In axSpA symmetric, thin and marginal syndesmophytes representing an ossification of enthesitic inflammation at the area of the attachment of the annulus fibrosus that may extend to the adjacent deeper layers anterior longitudinal ligament and are typical, while in DISH the so-called “chunky bridging osteophytes” grow as an additional layer on the anterior longitudinal ligament. Besides distinct anamnestic and clinical features, magnetic resonance imaging is helpful differentiating the two diseases since inflammatory changes with the typical pattern of axSpA are reliably visualized. Similar in both diseases is the high prevalence of vertebral fractures, which are mainly caused by the local osteoporosis and decreased flexibility of the affected bones, and therefore may occur even after minor traumata. The presence of extraarticular manifestations like uveitis, inflammatory bowel disease or psoriasis are only linked to axSpA. In contrast, DISH is associated with obesity, diabetes mellitus, and other metabolic diseases. Although DISH and axSpA are distinct conditions, the cooccurrence of these two diseases exists in some patients. Various therapeutic options are becoming available for axSpA, but no therapy has been approved for DISH yet.